Exploring the underlying mechanisms of Ashitaba in the management of non-alcoholic fatty liver disease by integrating the analysis of transcriptomics and metabolomics - Yang, Huan; Li, Yunshan; Xu, Weihong; Liu, Wenjuan; Xie, Ying (Frontiers in Medicine, 2023)
Ashitaba seems to improve glucose intolerance and decrease TG and TC, which contributes to the development of nonalcoholic fatty liver disease (NAFLD). However, it remains to be explored the mechanism of Ashitaba in managing NAFLD. We determined the impact of Ashitaba on NAFLD, particularly its underlying mechanisms at bioinformatic level. NAFLD established mouse model was treated with or without Ashitaba, and the underlying mechanism was explored, using transcriptomics paired with metabolomics. Ashitaba reduced obesity and liver steatosis in NAFLD mice. It was identified 429 differentially expressed genes (DEGs) and verified 45 differential metabolites, especially alleviate NAFLD via FXR signaling pathway. Our data may provide insight of the therapeutic impact of Ashitaba in the management of NAFLD, and may be useful in the clinical intervention for NAFLD.